Permeation of ethanol and water vapors through chitosan membranes with ferroferric oxide particles cross-linked by glutaraldehyde and sulfuric(VI) acid. Issue 15 (1st November 2016) - Dudek, Gabriela; Gnus, Małgorzata; Strzelewicz, Anna; Turczyn, Roman; Krasowska, Monika
ABSTRACT: Chitosan membranes filled with different amount of ferroferric oxides and cross-linked by two different agents, i.e. sulfuric acid or glutaraldehyde, were prepared and the influence of iron oxide and cross-linking agents on ethanol and water permeation has been discussed. Ethanol and water vapors permeation rates were determined using the measuring cell method and mass transport coefficients were evaluated. It was found that permeation of water for both types of chitosan membranes after addition of magnetite gradually increased. Furthermore, the difference between ethanol/water permeation coefficients was larger for glutaraldehyde cross-linked membranes (CHGA) than for sulfuric acid cross-linked membranes (CHSA).